Software Design and the Monkey's Brain. - Glass, Robert L. (Communications of the ACM, 2008)
The author discusses efforts to improve the design of computer software. During the 1980s Bill Curtis and Elliot Soloway were involved in separate projects aimed at improving the design process by identifying its fundamental nature. Their work revealed good software design to be a trial-and-error process dependent on the rapid, complex flow of human thought, and consequently not amenable to improvement via algorithms committed to paper. However, a promising sign is recent news about an experiment in which a monkey controlled a robot using brain signals.